Understanding multiple profiles of reading attitudes among adolescents. Issue 3 (27th May 2019) - Jang, Bong Gee; Henretty, Dawnelle
Abstract: In this article, the authors propose a model of four attitudinal profiles including both purpose (academic and recreational) and medium (print and digital): 1) recreational digital leaning/print averse reluctant readers, 2) avid digital readers, 3) avid print readers, and 4) digital leaning reluctant readers. We drew these four profiles of reading attitudes from our previous research where we analyzed survey data from approximately 5, 000 middle school students in the USA. We present prototypical adolescent reader from each profile guided by Valencia and Buly. Further, we suggested effective instructional practices that fit into each profile of adolescent readers.